Phenolic compounds from section Majorana (Mill.) Benth of Origanum L. species extracts via validated LC-MS/MS method - Carikci, Sema; Kilic, Turgut; Dirmenci, Tuncay; Goren, Ahmet C. (Acg Publications, 2022)
Origanum majorana L., (OM), O. onites L. (OO) and O. syriacum L. (subsp. bevanii (Holmes) Greuter & Burdet) (OS) are belong to Majorana (Mill.) Benth. section of Origanum L. genus. In this study, quantities of some phenolic compounds; gallic acid, syringic acid, p-hydory benzoic acid, caffeic acid, (E)-ferulic acid, chlorogenic acid, rosmarinic acid, pyrogallol and vanillin; in the chloroform (C), acetone (Ac) and methanol (M) extracts prepared from Origanum species collected from Turkiye were investigated via liquid chromatography and tandem mass spectrometry (LC-MS/MS). The relative standard deviations (RSD) of the phenolics were found as follows; 4.85, 8.39, 4.78, 8.04, 5.21, 5.45, 3.73, 5.47, respectively. Curcumin was used as an internal standard. In the extracts, (E)-ferulic acid and caffeic acid were found to be the most abundant compounds. O. syriacum was determined as the richest species in terms of phenolic acids.
Keywords: Origanum; section Majorana (Mill.) Benth.; Origanum majorana L.; O. onites L.; O. syriacum L. (subsp. bevanii (Holmes) Greuter & Burdet; LC-MS/MS